PARADIGMA ISLAM DALAM METODOLOGI PENELITIAN DAN IMPLIKASINYA TERHADAP PENELITIAN PENDIDIKAN AGAMA ISLAM - Tatang Hidayat; Abas Asyafah (Tadrib: Jurnal Pendidikan Agama Islam, 2018)
In principle, research is considered as an important thing in the realm of academics, especially for students and lecturers. However, in the reality, it is still easily found that many academia encounter difficulties in conducting research, especially in the field of Islamic education in which its paradigm is different compared to others. The purpose of this present study is to investigate the Islamic paradigm in research methodology and its implication for Islamic Education studies. This study employed a qualitative approach and literature review method. The collected data were analyzed thoroughly using a descriptive analysis method and in the same time, the writer also elaborated as well as provided understanding and explanation proportionally. Based on the results of the discussion, it is obvious that the Islamic paradigm appeared to be different from the paradigm developed by the western world in research methodology. The Islamic paradigm considers that science is not value-free. In addition, the Islamic paradigm has a special characteristic which is different from other paradigms. As a result, a researcher puts Islam as a fundamental paradigm in conducting research on Islamic Education and it in fact has implications for the research processes from the beginning to the end of the research, in relation to research intentions, finding problems, formulating the background of the research problems, formulating research problems, research objectives, research benefits, research theories, and research methodology. In particular, research methodology in this case covers bayani, burhani, tajribi, and 'irfani method. Similarly, all the processes covering data processing, data analysis, conclusions, research publication, research facilities, and all necessary things related to the research should always be associated with the commands and prohibitions as well as permission of Allah Subhanahu wa Ta’ala.